2022
DOI: 10.3390/ph15060707
|View full text |Cite
|
Sign up to set email alerts
|

MPMABP: A CNN and Bi-LSTM-Based Method for Predicting Multi-Activities of Bioactive Peptides

Abstract: Bioactive peptides are typically small functional peptides with 2–20 amino acid residues and play versatile roles in metabolic and biological processes. Bioactive peptides are multi-functional, so it is vastly challenging to accurately detect all their functions simultaneously. We proposed a convolution neural network (CNN) and bi-directional long short-term memory (Bi-LSTM)-based deep learning method (called MPMABP) for recognizing multi-activities of bioactive peptides. The MPMABP stacked five CNNs at differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 113 publications
1
7
0
Order By: Relevance
“…For the identification of neuroprotective peptides, the accuracy of MiCNN–LSTM was higher than the accuracy of both CNN and LSTM, confirming the validity of the combination of CNN and LSTM. A previous study used the CNN and LSTM based multi-dimensional algorithm to screen for peptides and the values of ACC reached 0.709 46 and 0.722, 51 respectively, which confirmed the high accuracy of the MiCNN–LSTM. This shows that the performance of the MiCNN–LSTM model is still greatly improved over the previous work.…”
Section: Discussionsupporting
confidence: 59%
“…For the identification of neuroprotective peptides, the accuracy of MiCNN–LSTM was higher than the accuracy of both CNN and LSTM, confirming the validity of the combination of CNN and LSTM. A previous study used the CNN and LSTM based multi-dimensional algorithm to screen for peptides and the values of ACC reached 0.709 46 and 0.722, 51 respectively, which confirmed the high accuracy of the MiCNN–LSTM. This shows that the performance of the MiCNN–LSTM model is still greatly improved over the previous work.…”
Section: Discussionsupporting
confidence: 59%
“…To further demonstrate the power of the ETFC model, we compare it with the existing methods. To improve the reproducibility and reliability of MPMABP ( Li et al 2022 ), MLBP ( Tang et al 2022 ), sequential properties-recurrent neural network (SP-RNN) ( Otović et al 2022 ) and PrMFTP ( Yan et al 2022 ), we provide the hyperparameter details of these models in Supplementary Tables S4–S7 , respectively. The comparison of ETFC with MPMABP, MLBP, SP-RNN, and PrMFTP is performed on the test set, and we randomly selected 80% of the set as the subset and repeated this process five times to obtain five subsets.…”
Section: Resultsmentioning
confidence: 99%
“…We compared our proposed method iMFP-LG with several state-of-the-art methods, including four conventional machine learning-based methods (CLR [12], RAKEL [34], RBRL [40] and MLDF [43]) and three deep learning-based methods (MPMABP [19], MFBP [31] and PrMFTP [42]). MPMABP and MFBP employed CNNs and RNNs for identifying multi-functional peptides.…”
Section: Imfp-lg Outperforms the State-of-the-art Methodsmentioning
confidence: 99%
“…Several works have made a difficult endeavor in discovery of multi-functional peptides. Tang et al [31] and Li et al [19] identified multi-functional peptides by using a multi-label deep learning method, which combines CNN and RNN to extract peptide features and assigns function labels separately. PrMFTP [42] improved the performance of multi-functional therapeutic peptide identification by employing multi-scale CNN, attention-based biLSTM.…”
Section: Introductionmentioning
confidence: 99%